2011
DOI: 10.1163/017353711x579849
|View full text |Cite
|
Sign up to set email alerts
|

Antipredator responses of two anurans towards native and exotic predators

Abstract: When faced with the risk of predation, tadpoles of many amphibian species are known to modify their phenotype. In this work we studied the effect of an exotic species, the red swamp crayfish (Procambarus clarkii), on the phenotype of two species of amphibians with different reproduction habitats: the Iberian painted frog, Discoglossus galganoi, that normally reproduces in temporary water bodies and the common toad, Bufo bufo, that reproduces in permanent water bodies. The responses were compared with the ones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(61 reference statements)
0
8
0
3
Order By: Relevance
“…One possible explanation in our case is that predator-induced changes in chemical defence exist in common toad tadpoles, but not in response to the specific predators we used. However, previous studies did document plastic changes in life-history traits, behaviour and morphology of common toad tadpoles to chemical cues on the presence of A. cyanea [38, 68], suggesting that they can detect their presence based on olfactory cues, perceive these predators as dangerous, and respond to them by changes in life-history traits. Because fishes are considered to be the most voracious predators of amphibian larvae [69], it is possible that in certain populations that live in permanent ponds, such as the one used in the current study, a relatively high baseline level of bufadienolide synthesis becomes fixed via selection [70].…”
Section: Discussionmentioning
confidence: 98%
“…One possible explanation in our case is that predator-induced changes in chemical defence exist in common toad tadpoles, but not in response to the specific predators we used. However, previous studies did document plastic changes in life-history traits, behaviour and morphology of common toad tadpoles to chemical cues on the presence of A. cyanea [38, 68], suggesting that they can detect their presence based on olfactory cues, perceive these predators as dangerous, and respond to them by changes in life-history traits. Because fishes are considered to be the most voracious predators of amphibian larvae [69], it is possible that in certain populations that live in permanent ponds, such as the one used in the current study, a relatively high baseline level of bufadienolide synthesis becomes fixed via selection [70].…”
Section: Discussionmentioning
confidence: 98%
“…Here, we present additional evidence of a reduction of swimming activity in tadpoles of the European brown frog when they are faced with the presence of water-borne chemical cues of an invasive slider turtle. Contrary to other studies that used the proportion of active tadpoles (Griffiths et al 1998;Awan & Smith 2007;McClure et al 2009;Almeida et al 2011;Nunes et al 2012;Pujol-Buxó et al 2013), spatial avoidance (Almeida et al 2011;Nunes et al 2012) or the number of movements (Polo-Cavia et al 2010) as a proxy of swimming activity, we used a more accurate approach by videotracking and analysing exact swimming trajectories and lengths, including path-shape parameters. We observed that tadpoles significantly reduced their swimming activity when chemical stimuli from the slider turtle were present in the water.…”
Section: Discussionmentioning
confidence: 99%
“…In natural systems, tadpoles spend their lives in a cocktail of chemical cues from potential predators and food sources. Previous research has reported examples of (1) frog species that only respond to predators that they would naturally experience in the wild (Kiesecker et al 1996;Griffiths et al 1998;PoloCavia et al 2010;Almeida et al 2011;Nunes et al 2012) and (2) species that shape their behaviour based on the presence of either native or alien predators (Almeida et al 2011;Nunes et al 2012). As we are aware, there is no report about amphibian species which respond to novel predators only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediterranean amphibians may be especially vulnerable to crayfish because many species are adapted to live in water bodies that dry out in summer and are naturally free from fish and other large predators (e.g. Beja & Alcazar, 2003;Ferreira & Beja, 2013), and thus may be less adapted to cope with crayfish predation than species living in permanent waters (Cruz, Rebelo, et al, 2006b;Nunes et al, 2011). This is supported by the lack of negative effects on P. perezi, which is known to thrive in permanent waters where predators are abundant (Beja & Alcazar, 2003;Cruz, Rebelo, et al, 2006b;Ferreira & Beja, 2013).…”
Section: Effects Of Biotic Interaction and Environmental Effects Onmentioning
confidence: 99%